Antiparasitic activity of the medicinal plant Dillenia suffruticosa against the marine leech Zeylanicobdella arugamensis (Hirudinea) and its phytochemical composition. (23rd October 2019) - Shah, Muhammad Dawood; Venmathi Maran, Balu Alagar; Iqbal, Mohammad; Ching, Fui Fui; Mohamad Lal, Mohammad Tamrin; Binti Othman, Rafidah; Shapawi, Rossita
Abstract: Zeylanicobdella arugamensis (Annelida: Hirudinea), a marine parasitic leech, is currently affecting different species of cultured groupers, hybrid groupers, snappers and sea bass in Malaysia. Dillenia suffruticosa (Dilleniaceae), a medicinal plant found in Sabah, has been selected in our experiment to kill the leeches as a natural control method. The leech‐infested hybrid groupers were collected from aquaculture facilities, and the isolated leeches were challenged against methanol extract of D. suffruticosa leaves. The experiment was carried out using various concentrations of the extracts such as 25, 50 and 100 mg/ml. The methanol extract showed significant antiparasitic activity against Z. arugamensis with 100% mortality at a concentration of 100 mg/ml in 14.39 ± 3.75 min., followed by 50 and 25 mg/ml in 32.97 ± 9.29 and 41.77 ± 5.40 min., respectively. The phytochemical composition of the extract was determined using GC‐MS analysis to understand the nature of the principal compounds responsible for its antiparasitic properties. The leaves of D. suffruticosa demonstrated the presence of different bioactive compounds of various natures with varying percentages. Thus, it could be revealed that the methanol extract of D. suffruticosa mainly contains vital phytochemical compounds and showed an effective antiparasitic activity against the harmful leeches of hybrid groupers.